Retelling Inclusive Schooling: The UN’s CRPD Committee in Selected Countries - Winzer, Margret; Mazurek, Kas (International Dialogues on Education Journal, 2022)
This paper targets the principle of full inclusion as articulated by Article 24 of the Convention on the Rights of Persons with Disabilities and General Comment #4 through an analysis of the CRPD Committee’s Concluding Observations for Poland, Germany, and Australia. We find inherent tensions and dialectical contradictions between the ideals of full inclusion embodied in Article 24 and the reluctance of the State Parties to meet the targets. To date, the obligations entailed by Article 24 have failed to retrofit education systems.